Phenomenological nuclear density distributions - Lalazissis, G. A.; Panos, C. P. (HNPS Advances in Nuclear Physics, 2020)
A recently proposed semiphenomenological density distribution for neutrons and protons in nuclei is discussed. This density was derived using the separation energies of the last neutron or proton. A comparison is made with the symmetrised Fermi density distribution with parameters determined by fitting electron scattering experimental data and with a Fermi density with parameters coming from a recent analysis of pionic atoms. Theoretical expressions for rms radii for neutron, proton and matter distributions are proposed, which give the average trend of the variation of these quantities as functions of Ν, Ζ and A respectively. To facilitate the use of the new density all the parameters needed in a practical application are tabulated for a series of nuclei. Some applications of the new density are also discussed.